2002
DOI: 10.1074/jbc.m207841200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 16-Nucleotide Sequence That Mediates Post-transcriptional Regulation of Rat CYP2E1 by Insulin

Abstract: Insulin directly down-regulates the gene expression of the rat CYP2E1 by altering its mRNA stability (De Waziers, I., Garlatti, M., Bouguet, J., Beaune, P. H., and Barouki, R. (1995) Mol. Pharmacol. 47, 474 -479). Because the regulation of CYP mRNA stability was poorly understood, the molecular mechanisms involved in this regulation in the rat hepatoma H4IIEC3 cell line were studied. By using RNase T1 protection methods, the formation of a major CYP2E1 RNA-protein complex was observed. By competition experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
1
24
1
1
Order By: Relevance
“…The cause of the loss of CYP2E1 activity was unclear. Its inhibition by insulin has been reported in a rat hepatoma cell line (Moncion et al, 2002). However, medium depletion or lower concentrations of insulin did not prevent CYP2E1 activity loss in HepaRG cells (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…The cause of the loss of CYP2E1 activity was unclear. Its inhibition by insulin has been reported in a rat hepatoma cell line (Moncion et al, 2002). However, medium depletion or lower concentrations of insulin did not prevent CYP2E1 activity loss in HepaRG cells (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…Mean ± SE; ⁎ P b 0.025; ⁎⁎ P b 0.005; ⁎⁎⁎ P b 0.001. group of diverse xenobiotics may increase the expression of CYP2E1 by increasing its transcription or translation, pathophysiological conditions, such as disturbances in carbohydrate metabolism, may up-regulate the gene by both transcriptional and post-transcriptional mechanisms (Dong et al, 1988;Thummel and Schenkman, 1990;Novak and Woodcroft, 2000;Moncion et al, 2002). Insulin can reverse the up-regulation of CYP2E1 in diabetes suggesting that this endogenous signaling pathway is involved in the regulation (Moncion et al, 2002). The data of this study add to the complexity of the CYP2E1 regulation by demonstrating that another endogenous signaling pathway, a D 2 -dopaminergic receptor pathway, is also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that endogenous processes and signaling pathways may play a role in the regulation of CYP2E1. For example, disturbances in glucose metabolism and an insulindependent signaling pathway may influence the hepatic levels of CYP2E1 (Woodcroft et al, 2002;Moncion et al, 2002). Recent evidence also showed that increased noradrenergic neurotransmission was associated with increased CYP2E1-catalyzed pnitrophenol hydroxylation (PNP), suggesting the involvement of catecholamines in the regulation of this isozyme (Konstandi et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Cytochrome P450 2E1 (CYP2E1) metabolises many endogenous or exogenous small molecules such as acetone, glycerol, ethanol, acetaminophen, carbon tetrachloride, halothane or nitrosamines [1][2][3]. Hepatic expression of the CYP2E1 mRNA and/or expression of the CYP2E1 protein are increased in different physiological or pathological conditions, such as fasting, a high fat diet, diabetes, obesity or ethanol intoxication [1,4].…”
Section: Introductionmentioning
confidence: 99%